Probing effective loop quantum gravity on weak gravitational lensing, Hawking radiation and bounding greybody factor by black holes - Javed, Wajiha; Atique, Mehak; Övgün, Ali (Springer/Plenum Publishers, 2022)
In this paper, we study the weak deflection angle of black hole in effective loop quantum gravity using the geometrical technique used by Gibbons and Werner. We first derive the optical metric, calculate the Gaussian optical curvature, and then apply the Gauss-Bonnet theorem. We then also investigate the effect of plasma and dark matter mediums on the weak deflection angle. We show that increasing the impact of these two mediums grows the deflection angle. We also calculate the Hawking temperature via Gauss-Bonnet theorem. In addition, we determine the fermionic greybody bounds. Moreover, we discuss the graphical behaviour of the deflection angle and bounds on the greybody factor. Graphically, we observe that taking 0 < A(lambda) < 1 angle ranges from negative values to maximum values and also attain maximum value for these values of A(lambda) and for A(lambda) >= 1 exponentially approaches to zero. Later, we graphically investigate that the greybody factor bound exhibits the convergent behaviour by converging to 1. We also examine that the results obtained for the black hole in effective loop quantum gravity are reduced to the Schwarzschild black hole solutions when the dimensionless non-negative parameter is equal to zero A(lambda) = 0.
Keywords: General relativity; Black hole; Deflection angle; Hawking radiation; Plasma medium; Gauss-Bonnet theorem; Greybody factor